2002
DOI: 10.1002/ccd.10098
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of vasoseal and angioseal closure devices in patients undergoing coronary angiography and angioplasty

Abstract: AngioSeal (AS) and VasoSeal (VS) are collagen-based arterial closure devices utilized to achieve earlier hemostasis and ambulation in diagnostic and interventional percutaneous procedures. To our knowledge, there has been no randomized studies comparing these two devices as approved for use in the United States. One hundred fifty-seven patients were randomized to receive either the 8 Fr AS (n = 79) or VS (n = 78) closure device. Data on 95 patients who had coronary angiography (49 AS, 46 VS) and 55 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 11 publications
0
17
2
1
Order By: Relevance
“…In the STAND II trial [14] a median time to hemostasis of 19 min was reported using the Perclose device vs 243 min using manual compression after coronary angiography. Shammas et al reported a time to hemostasis of 20 min on average using VasoSeal and AngioSeal [11]. The reasons for this discrepancy, particularly between the STAND II trial and our report, are not evident.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the STAND II trial [14] a median time to hemostasis of 19 min was reported using the Perclose device vs 243 min using manual compression after coronary angiography. Shammas et al reported a time to hemostasis of 20 min on average using VasoSeal and AngioSeal [11]. The reasons for this discrepancy, particularly between the STAND II trial and our report, are not evident.…”
Section: Discussioncontrasting
confidence: 81%
“…Regarding the aggressive anticoagulation therapy and the modern platelet inhibition therapy, Cura et al achieved a technical success rate of 93.6% in patients treated with glycoprotein IIb-IIIa receptor antagonists [15]. Deployment failure of AngioSeal and VasoSeal has been reported higher in up to 7.7 and 5.2% of cases, respectively [11], which indicates a slight advantage for using the Perclose devices. The success rate of manual compression is obviously high and is reported to be approximately 98.9% in the literature [14].…”
Section: Discussionmentioning
confidence: 95%
“…As myriad previous studies clearly demonstrated shorter times to hemostasis with different femoral closure devices compared to manual/ mechanical compression 13 , we decided not to include a control group treated with manual compression [14][15][16][17][18][19] . Given the inconsistent data in regard to possible differences in time to hemostasis between diagnostic and interventional procedures 16,20,21 , we observed no such difference in time to hemostasis in our study. This is in accordance with previous reports for the FemoSeal® system for the closure of smaller arterial puncture sites and might be interpreted as an additional safety aspect.…”
Section: Discussioncontrasting
confidence: 73%
“…Advancement in technology over the past decade has seen the introduction of vascular closure devices 14,30 to minimise bleeding and haematoma formation and allow early ambulation. However, this method of active closure has not been widely adopted.…”
Section: Introductionmentioning
confidence: 99%